Population dynamics, size hierarchy and neighbour interactions of early colonizing vascular plants in a Norwegian glacier foreland - Dalen, Anne Marie (2015)
The population dynamics of the three early colonizing plant species Saxifraga stellaris, Arabis alpina and Cerastium cerastoides was studied in the Hellstugubreen glacier foreland in Jotunheimen National Park in southern central Norway, with particular emphasis on competitive interactions. The species were first observed on terrain exposed for minimum six years. Their density then increased, reaching a peak at 11-40 years, at a distance of 100- 400 m from the glacier front. Density then decreased, and the species finally disappeared in areas exposed for 50-70 years or more, except for a few riverbeds. The relative abundance of the species differed significantly, with S. stellaris seven times more abundant than the least abundant A. alpina. There was a strong positive relationship between individual size and fertility in all three species, and the frequency of fertile individuals in the populations increased with time. While 93 % of S. stellaris individuals were fertile already in terrain exposed for only 6-8 years, rising to 98 % after 17-21 years, C. cerastoides only had 37 % fertile individuals in terrain exposed 6-8 years, rising to 80 % after 17-21 years. Fertility in A. alpina rose form 38 % to 65 % in the same interval. The size frequency distributions of the species were strongly positively skewed throughout the first 21 years since deglaciation, revealing no sign of competitive interactions. Similarly there was no or only a weak correlation between the performance (size, fertility) of an individual plant and the number and size of neighbours. The species most frequently physically touching above ground or actually sharing growth site with the study species were mostly other pioneers throughout the foreland. The pioneer species occurred mainly in sample squares with low overall plant cover value (1-10 %), but in older parts of the foreland, squares where the pioneer species was present had cover value above the average cover in the same areas. The results suggest that competition is unlikely to play a significant role in the species substitution process in middle-alpine vegetation successions.